The Role of Radiology in Progressive Fibrosing Interstitial Lung Disease - Abu Qubo, Ahmad; Capaccione, K. M.; Bernstein, Elana J.; Padilla, Maria; Salvatore, Mary (Frontiers in Medicine, 2022)
In this article, we describe the role of radiology for diagnosis and follow-up of progressive fibrosing interstitial lung disease (PF-ILD). Patients with PF-ILD are at increased risk for early death without treatment. Clinical diagnosis of PF-ILD has been described in the literature. Here, we review the radiographic diagnosis of PF-ILD and the unique CT characteristics based on specific types of fibrosis. Ultimately, we conclude that radiology has the potential to recognize progression early and thus make an important contribution to the multidisciplinary discussion for this important diagnosis.